Description of Elementary School Age Children's Behavior in View of Dental and Oral Hygiene Status - Rahayu, Eka Sri; Qathrunnada, Qathrunnada; Nurdin, Nurdin (Journal Dental Health, 2023)
Dental and oral health is a part of body health that cannot be separated from one another because it will affect overall body health. The aim of this research is to understand the behavior of elementary school age children in terms of dental and oral hygiene status. The type of research used is descriptive research. The population in this study was all 23 students in class IV and 10 students in class V, namely 33 students. Determining the sample in this study used the total population technique. The research results found that the majority of respondents were male (58%), had good knowledge (79%), poor attitudes (67%) and poor actions (73%).